Feasibility of using rubber waste fibers as reinforcements for sandy soils - Meddah, Abdelaziz; Merzoug, Karima (Université de M'sila, 2017)
In this study, an alternative and environmentally friendly method for the reinforcement of dune sand is proposed. This technique consists of using randomly distributed rubber fibers to improve the engineering properties of sand. Rubber fibers are added to the sand with different percentages: 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75 and 2% of dry weight of sand. The experimental program carried out consists of investigating the effect of rubber fibers on the shear strength properties of sand. Reinforced and unreinforced samples are tested in the dense as well as loose state. The results obtained showed that the inclusion of rubber fibers in dune sand will improve the engineering properties of various civil engineering applications such as shallow foundations and slope. Therefore, incorporation of rubber fibers can enhance the shear strength characteristics, peak and residual strengths, and introduce more ductility to the mechanical behavior of sand. In addition to the technical effect, this paper emphasizes another environmentally attractive option, which is the use of rubber fibers as reinforcements for granular soils as this helps to remove some parts of these wastes and protect the environment.
Keywords: Rubber waste Fibers Reinforcement Dune sand Shear strength Valorization